Europeanization processes regarding matters of cybersecurity: The case of Portugal - Alexandre, Pedro Miguel (2021)
In a world that receives technology with open arms, the issue of cybersecurity has increasingly become a daily reality and it is necessary to treat it as something essential for the protection of our online presence. Not only in terms of secure internet browsing practices, but also in the implementation of actions that are ready to tackle new and unknown threats: several countries have paid attention to these changes and modified their security policies. In this sense, we intend to use Europeanization in order to understand, in the sphere of European integration, how the European Union affects and influences its Member States in the formulation of measures related to the cybersecurity of its citizens. Hence, Portugal will be used as a case study. This choice stems from the fact that this country contains an unexplored volume of academic literature regarding the topic, in comparison with other larger ones. Therefore, the main objective of this work is precisely to provide a new view on how the EU has shaped the legislative process of a small country, but important nonetheless in its position on the European panorama.